1973
DOI: 10.3758/bf03198075
|View full text |Cite
|
Sign up to set email alerts
|

Processing demands of sequential information

Abstract: Three experiments examined the processing capacity required to use sequential information in a serial reaction time task with partially predictable sequences. The first two experiments varied the response stimulus interval (RSI) between o and 500 msec and found the relative advantage of the high-probability stimulus to be independent of the length of the RSI. The third experiment compared utilization of sequential information either with or without a secondary task. The secondary task did not affect the high-p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
11
0

Year Published

1975
1975
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 18 publications
1
11
0
Order By: Relevance
“…Finally, we should note that in Experiment 1 we found that memory load, regardless of its type, increased the size of the color-response repetition benefit. A similar effect was reported by Keele and Boies (1973) in the context of a task requiring participants to quickly report sequences of target locations while remembering five consonants. However, in Experiment 2, this effect disappeared.…”
Section: Discussionsupporting
confidence: 71%
“…Finally, we should note that in Experiment 1 we found that memory load, regardless of its type, increased the size of the color-response repetition benefit. A similar effect was reported by Keele and Boies (1973) in the context of a task requiring participants to quickly report sequences of target locations while remembering five consonants. However, in Experiment 2, this effect disappeared.…”
Section: Discussionsupporting
confidence: 71%
“…Although memory load typically has a strong effect on performance in both the primary task and the memory task itself, it does not interact with a whole number of manipulations of perceptual factors (e.g., stimulus brightness or quality), attentional factors (e.g., array size or cuing), and decisional or response-related factors (e.g., yes-no decision or S-R compatibility) (for an overview, see Logan, 1980). Interestingly, however, memory load does interact with some factors that are likely related to S-R translation, such as response-set size (Logan, 1979), S-R mapping-rule complexity (Logan, 1980), or stimulus predictability (Keele & Boies, 1973). This suggests that, as Logan (1980) has pointed out, the digit-memory task uses up capacity from the same system or medium that prepares and holds S-R mapping rules, possibly by interfering with rehearsing the rules before the trial (Pashler, 1994).…”
Section: Methodsmentioning
confidence: 95%
“…Experimental support for the notion of decay has been found by several researchers who observed decreasing repetition effects with an increasing RSI (Bertelson, 1961;Bertelson & Renkin, 1966;Hale, 1967;Smith, 1968;Umilta et al, 1972). There are, however, other researchers who found little or no effect of a changing RSI on the repetition effect (Keele, 1969;Keele & Boies, 1973;Schvaneveldt & Chase, 1969). These seemingly conflicting results can be ascribed to other variables such as stimulus-response compatibility, practice, and number of alternatives, whose influences are often compounded with RSI influences.…”
Section: Methodsmentioning
confidence: 98%
“…The actual RSI of Kirby would then probably exceed 200 ms, which explains the finding of an expectancy effect. The same confusing methodology was also used by other researchers (e.g., Bertelson & Renkin, 1966), and sometimes the actual RSI was additionally prolonged with the warming-up time of the presented stimuli when incandescent lamps were used (Keele & Boies, 1973). Apart from methodological differences, the influence of RSI has often been compounded with the influence of other variables, such as stimulusresponse compatibility, practice, and number of alternatives.…”
mentioning
confidence: 97%